2021
DOI: 10.54536/ajaset.v5i2.66
|View full text |Cite
|
Sign up to set email alerts
|

System Requirement Specification of Mobile Apps for shrimp farming in Shyamnagar of Bangladesh

Abstract: Frozen food is one of Bangladesh’s most valuable export items, comprising more than 80% of shrimp. The most cultivated area of shrimp is situated in the southern region of Bangladesh. This research was carried out to identify the core problem in the shrimp farming areas in order to support the related farmers in seeking a solution through the most common technology used by them. The study was conducted in Shyamnagar, Satkhira district with a total of 40 female respondents involved. This research showed that sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Preserving the proper physicochemical parameters contributes to the preservation of health and development in the density of the species. On the other hand, it is concluded that having poor-quality pond water will cause a severe problem for the fish since it will contribute to reducing the defenses against viral and bacterial infections and more diseases that could cause the death of the biological entity [3]. Therefore, maintaining the physicochemical parameters that preserve water quality and contribute to protecting the species represents a challenge for technology.…”
Section: Introductionmentioning
confidence: 99%
“…Preserving the proper physicochemical parameters contributes to the preservation of health and development in the density of the species. On the other hand, it is concluded that having poor-quality pond water will cause a severe problem for the fish since it will contribute to reducing the defenses against viral and bacterial infections and more diseases that could cause the death of the biological entity [3]. Therefore, maintaining the physicochemical parameters that preserve water quality and contribute to protecting the species represents a challenge for technology.…”
Section: Introductionmentioning
confidence: 99%
“…As the development of communication technologies are expanding day by day, resources of original information become not plentiful. It is necessary to acquire adequate knowledge on the System Requirement Specification (SRS), a structured collection of information that embodies the requirements of a system for implementing any communication tools (Hasan et al, 2021). But the communication specifications are not easy and not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…The fish farmers face many challenges during the culture period because of poor water quality which leads to disease and increases mortality 2 in aquatic animals. Abnormal water quality is a major issue in the aquaculture system, and consequently, fish loses their natural defence against bacterial, viral, fungal and parasitic infections 3 . Nowadays, water management in aquaculture farm has become a crucial part of global environment conservation as climate change is affecting the water parameters adversely 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Abnormal water quality is a major issue in the aquaculture system, and consequently, fish loses their natural defence against bacterial, viral, fungal and parasitic infections. 3 Nowadays, water management in aquaculture farm has become a crucial part of global environment conservation as climate change is affecting the water parameters adversely. 4,5 The farming stakeholders need a smart solution to achieve food security in aquaculture production by battling global heating which is affecting water and fish quality.…”
Section: Introductionmentioning
confidence: 99%